THE FEEDING AND PHYSICAL GROWTH OF THE SCHOOL CHILDREN WITH THE HIGHER LEVEL OF THE BONE TISSUE MINERALIZATION - T.Yu. Vishnevetskaya; A.Yu. Makarova; Zh.Yu. Gorelova ("Paediatrician" Publishers LLC, 2007)
The article analyzes feeding organization and quality for the children aged between 10 and 16 with the higher level of the bone tissue mineralization. The authors noted down the radical excess of the ration calorie content together with the excess of the protein and especially fat components. The researchers revealed the reduced content of the main vitamins, which contributes to the increase of the bone tissue mineralization levels among children and change in their morphofunctional status with the obesity development. in the given situation, it is necessary to speak of the ration correction according to the main components and distribution of its daily calorie content, as well as the ration supplements by introducing missing vitamins, which the polyvitaminic complexes may prove to be a good alternative to. Key words: children, bone tissue mineralization, food ration, vitamins.